In search of Christ in Latin America from colonial image to liberating savior - Escobar, Samuel 1934-2025; Padilla, C. René 1932-2021 (Downers Grove, Illinois IVP Academic, 2019)
From the poor Christ to Christ of the poor -- The Iberian Christ who crossed the oceans -- That other Christ of the Indians -- Christ in early Protestant preaching -- The beginnings of an Evangelical Latin American Christology -- Christ in Ecumenical Protestant thought -- Christology in times of revolution -- A Christological renewal in Catholicism -- Jesus Christ and the revolutionaries -- The kingdom of God -- Latin America enters the theological scene -- Christ in Latin American culture once again -- Jesus Christ's new time for reflection and dialogue -- Jesus and the lifestyle and mission of the kingdom -- With Jesus in global mission -- Present directions of Evangelical theological reflection.
Includes index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Person and offices; Evangelicalism -- Latin America -- History -- 20th century